A Qualitative Study on the Dynamics of Same-Sex Behavior Among Male Adolescents in Banjarmasin - Rahman, Raden Topan Aditya; Yuandari, Esti (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2025)
The phenomenon of men who have sexual relations with other men, commonly referred to as men who have sex with men (MSM), has existed for a long time. Generally, MSM engage in same-sex relations influenced by factors such as momentary sexual urges or impulses. In Indonesia, the MSM population is currently expanding, including in the city of Banjarmasin. This qualitative study employs a case study design to examine the dynamics of sexual deviance among male adolescents in Banjarmasin and to explore local government policies and programs aimed at addressing the increasing cases of MSM. Data were collected using snowball sampling from male adolescent participants who exhibit such behaviors. Findings indicate that causes of sexual deviance among male adolescents include lack of parental attention and an unsupportive environment in personality development. Emotional attachment and affection received from the same sex act as triggers for emotional changes, with romantic relationships among peers of the same sex perceived as more enjoyable and challenging. The results of this study are expected to provide a foundation for local governments to formulate effective policies and legal frameworks to prevent sexual deviant behavior that could harm youth, who are the pillars and future generation of the nation.